# |
ODE |
Mathematica |
Maple |
\[
{}y x^{\prime }+\left (1+y \right ) x = {\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y+\left (2 x -3 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-2 x^{4}-2 y = 0
\] |
✓ |
✓ |
|
\[
{}1 = \left ({\mathrm e}^{y}+x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{2} x^{\prime }+\left (y^{2}+2 y \right ) x = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 5 y+x +1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y-2 x y-2 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}2 y+\left (1+x \right ) y^{\prime } = \frac {{\mathrm e}^{x}}{1+x}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right )^{2}+\left (x -\tan \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y = \left (y^{4}+x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\cos \left (\theta \right ) r^{\prime } = 2+2 r \sin \left (\theta \right )
\] |
✓ |
✓ |
|
\[
{}\sin \left (\theta \right ) r^{\prime }+1+r \tan \left (\theta \right ) = \cos \left (\theta \right )
\] |
✓ |
✓ |
|
\[
{}y x^{\prime } = 2 y \,{\mathrm e}^{3 y}+x \left (3 y +2\right )
\] |
✓ |
✓ |
|
\[
{}y^{2}+1+\left (2 x y-y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right )-\sec \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}y+y^{3}+4 \left (x y^{2}-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y-x y-3+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+2 \left (x -2 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime }+\left (x^{2}-1\right )^{2}+4 y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime } y^{2}-x y^{3} = {\mathrm e}^{\frac {x^{2}}{2}} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{3} y^{\prime }+y^{4} x = x \,{\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}\cosh \left (y\right ) y^{\prime }+\sinh \left (y\right )-{\mathrm e}^{-x} = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (\theta \right ) \theta ^{\prime }+\cos \left (\theta \right )-t \,{\mathrm e}^{-t} = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y = \sqrt {y}\, x \,{\mathrm e}^{x^{2}}
\] |
✓ |
✓ |
|
\[
{}t x^{\prime }+x \left (1-x^{2} t^{4}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y^{2} = x y
\] |
✓ |
✓ |
|
\[
{}\csc \left (y\right ) \cot \left (y\right ) y^{\prime } = \csc \left (y\right )+{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y = \frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{2} x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}r^{\prime }+\left (r-\frac {1}{r}\right ) \theta = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 3 x^{3} y^{{4}/{3}}
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime }+\frac {2 y}{1+x} = \frac {x}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right ) y^{\prime }+\left (\sin \left (y\right )-1\right ) \cos \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (x \tan \left (y\right )^{2}+x \right ) y^{\prime } = 2 x^{2}+\tan \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = y^{3} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y+y^{\prime } = y^{2} {\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \left (1-{\mathrm e}^{2 y-x^{2}}\right )
\] |
✓ |
✓ |
|
\[
{}2 y = \left (x^{2} y^{4}+x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}1+x y \left (x y^{2}+1\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }+x y = x \left (-x^{2}+1\right ) \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime }-1-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (x y+x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +y-\left (x -2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \ln \left (x \right ) y^{\prime }+y-x = 0
\] |
✓ |
✓ |
|
\[
{}x -2 y+1+\left (y-2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y-2 x y^{3}+x^{3}+\left (x^{2}+y^{2}-3 x^{2} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 \,{\mathrm e}^{x}-t^{2}+t \,{\mathrm e}^{x} x^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}6+2 y = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x -3 y = \left (3 y-x +2\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y \sin \left (x \right )-2 \cos \left (y\right )+\tan \left (x \right )-\left (\cos \left (x \right )-2 x \sin \left (y\right )+\sin \left (y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y-\left (y^{3}+x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = 2 y^{\prime }+2 y^{2}
\] |
✓ |
✓ |
|
\[
{}\tan \left (y\right ) = \left (3 x +4\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \ln \left (y\right ) \tan \left (x \right ) = 2 y
\] |
✓ |
✓ |
|
\[
{}2 x y+y^{4}+\left (x y^{3}-2 x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y+\left (3 x -2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}r^{\prime } = r \cot \left (\theta \right )
\] |
✓ |
✓ |
|
\[
{}\left (4 y+3 x \right ) y^{\prime }+y+2 x = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{3}-y^{3}-3 x +3 y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y-\sqrt {x^{2}+y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \cos \left (y\right ) \cos \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}x +y+\left (2 x +3 y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+{\mathrm e}^{\frac {x}{y}}+{\mathrm e}^{\frac {x}{y}} \left (1-\frac {x}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x +y \cot \left (x \right ) = 0
\] |
✓ |
✓ |
|
\[
{}3 x -6 = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x -2 x y+{\mathrm e}^{y}+\left (y-x^{2}+x \,{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime }-y+\frac {x^{2}}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y \left (1+y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y \sqrt {x^{2}+y^{2}}+x y = x^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}3 \,{\mathrm e}^{x} \tan \left (y\right ) = \left (1-{\mathrm e}^{x}\right ) \sec \left (y\right )^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\sec \left (y\right )^{2} y^{\prime } = \tan \left (y\right )+2 x \,{\mathrm e}^{x}
\] |
✓ |
✗ |
|
\[
{}2 x \tan \left (y\right )+3 y^{2}+x^{2}+\left (x^{2} \sec \left (y\right )^{2}+6 x y-y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \cos \left (\frac {x}{y}\right )-\left (y+x \cos \left (\frac {x}{y}\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (3 x^{2}+y\right )-x \left (x^{2}-y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +\left (2 x +3 y+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-5 y-x \sqrt {y} = 0
\] |
✓ |
✓ |
|
\[
{}x \sqrt {1-y}-y^{\prime } \sqrt {-x^{2}+1} = 0
\] |
✓ |
✓ |
|
\[
{}x y-y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \,{\mathrm e}^{-y^{2}}+y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 y^{3}-2 x^{2} y^{3}-x +x y^{2} \ln \left (y\right )}{x y^{2}}+\frac {\left (2 y^{3} \ln \left (x \right )-x^{2} y^{3}+2 x +x y^{2}\right ) y^{\prime }}{y^{3}} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-2 y-2 y^{3} x^{4} = 0
\] |
✓ |
✓ |
|
\[
{}\left (-2 x^{2}-3 x y\right ) y^{\prime }+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{4}+4 y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x^{3} y^{6}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x+x^{2} {\mathrm e}^{\theta }
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2} = 2 x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}3 x y+\left (3 x^{2}+y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y+y^{\prime } = 3 \,{\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}4 x y^{2}+\left (x^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x -2 y+3 = \left (x -2 y+1\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (x^{3}-2 x y\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}2 x y-2 y+1+x \left (x -1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}+2 x^{2} y+\left (-3 x^{3}-2 x y^{2}\right ) y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}2 \left (x^{2}+1\right ) y^{\prime } = \left (2 y^{2}-1\right ) x y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+P \left (x \right ) y = Q \left (x \right )
\] |
✓ |
✓ |
|
\[
{}4 y^{2} = x^{2} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+\left (x +y\right ) y^{\prime }+1 = 0
\] |
✓ |
✓ |
|
\[
{}1+\left (2 y-x^{2}\right ) {y^{\prime }}^{2}-2 y {y^{\prime }}^{2} x^{2} = 0
\] |
✗ |
✗ |
|